EKEKTIFITAS PENGGUNAAN METODE THINK-PAIR SHARE DAN SNOWBALL THROWING UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR ALJABAR LINEAR - Yuniansyah; Yonhendri; Barovih, Guntoro (Information Technology Education Department, 2025)
The purpose of this study is to find out how effective Think-Pair-Share (TPS) and snowball shooting learning methods are to improve students' motivation and their learning outcomes in Linear Algebra course at Palcomtech Institute of Technology and Business. A two-cycle Classroom Action Research (PTK) using planning, implementation, observation, and reflection. The subjects of this study were 22 students of S1 Information Systems class who have been working and facing various problems in their learning process. It was hoped that these two methods would allow students to more actively participate in the lessons and improve their understanding of the material being taught. The results showed that from cycle I to cycle II, the number of students who obtained a score of at least 81 increased significantly. TPS and Snowball throwing methods proved effective in improving students' motivation and their learning outcomes. This method can also be applied to other courses, especially those related to science and technology.